2004
DOI: 10.1128/jcm.42.1.484-486.2004
|View full text |Cite
|
Sign up to set email alerts
|

Osteosynthesis-Associated Bone Infection Caused by a Nonproteolytic, Nontoxigenic Clostridium botulinum -Like Strain

Abstract: A nonproteolytic, nontoxigenic Clostridium botulinum strain identified by conventional and molecular techniques as type B-, E-, or F-like (BEF-like) was isolated from a human postsurgical wound. All previous reports of such strains have been from environmental sources. Since toxin production is the main taxonomic denominator for C. botulinum, a new name is needed for nonproteolytic, nontoxigenic BEF-like clinical isolates. CASE REPORTA 50-year-old man was hospitalized in June 2002 for an open supracondylar fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The nucleotide sequence of the 16S rRNA gene of strain A1336 T was determined as described previously (Carlier et al, 2004). For comparative phylogenetic and sequence similarity analysis, 16S rRNA gene sequences from all species in the family Prevotellaceae were retrieved from the EzTaxon database (Kim et al, 2012).…”
mentioning
confidence: 99%
“…The nucleotide sequence of the 16S rRNA gene of strain A1336 T was determined as described previously (Carlier et al, 2004). For comparative phylogenetic and sequence similarity analysis, 16S rRNA gene sequences from all species in the family Prevotellaceae were retrieved from the EzTaxon database (Kim et al, 2012).…”
mentioning
confidence: 99%
“…Colony morphology and the responses of the strains to special potency disks (Jousimies-Somer et al, 2002) were observed on Columbia sheep blood agar plates. For further characterization, the novel strains were maintained anaerobically in trypticase/glucose/yeast extract (TGY) medium under anaerobic conditions at 37 u C, as described previously (Carlier et al, 2004). Biochemical reactions were performed according to the procedures of the VPI Anaerobe Laboratory Manual (Holdeman et al, 1977) by using trypticase/yeast extract (TY) medium supplemented with 1 % (w/v) of each sterilized substrate.…”
mentioning
confidence: 99%
“…It is interesting that among closely related strains of C. botulinum type B there was also one strain of type E, which confirms panmictic nature of the anaerobe. The high similarity between C. botulinum and C. botulinum-like strains was also observed by Carlier et al (2004) taking into account 16S rDNA sequence. The similarity between C. botulinum type B (ATCC 25765) and C. botulinum-like strain AIP 355.02 reached the level of 93%.…”
Section: Discussionmentioning
confidence: 71%